2011 IEEE Fifth International Conference on Self-Adaptive and Self-Organizing Systems 2011
DOI: 10.1109/saso.2011.25
|View full text |Cite
|
Sign up to set email alerts
|

The Axiomatisation of Socio-Economic Principles for Self-Organising Systems

Abstract: Abstract-We are interested in engineering for open, embedded and resource-constrained systems, which have applications in ad hoc, sensor and opportunistic networks. In such systems, there is decentralised control, competition for resources and an expectation of both intentional and unintentional errors. The 'optimal' distribution of resources is then less important than the 'robustness' or 'survivability' of the distribution mechanism, based on collective decision-making and tolerance of unintentional errors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…This can be seen as instance of the more general methodology of value-sensitive design [16] [17], a methodology for engineering socio-technical systems which promotes human values as "supra-functional requirements". Further examples of this can be seen in what could be considered as, effectively, sustainability by design , in systems which try to encapsulate Ostrom's design principles for self-governing institutions which support sustainable common-pool resource management [32] through an axiomatisation in (executable) computational logic.…”
Section: Social Valuesmentioning
confidence: 99%
“…This can be seen as instance of the more general methodology of value-sensitive design [16] [17], a methodology for engineering socio-technical systems which promotes human values as "supra-functional requirements". Further examples of this can be seen in what could be considered as, effectively, sustainability by design , in systems which try to encapsulate Ostrom's design principles for self-governing institutions which support sustainable common-pool resource management [32] through an axiomatisation in (executable) computational logic.…”
Section: Social Valuesmentioning
confidence: 99%
“…Ostrom's eight principles constitute conditions for overcoming the tragedy. The principles are as follows (see [8] When considering open distributed systems, we aim to implement organisations which follow those principles as shown in the next section.…”
Section: Why Social Awareness And/or Self-awareness Mattersmentioning
confidence: 99%
“…She presented eight design principles for successful self-management of decentralised institutions. Pitt et al [8] adapted these to Normative Multi-Agent Systems (see Sect. 4.2.3 above in this chapter).…”
Section: Normative Multi-agent Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pitt et al (2012), it was shown how the framework of dynamic norm-governed systems could be used to axiomatise Ostrom's institutional design principles in computational logic using the Event Calculs (cf. Sect.…”
Section: Self-organising Electronic Institutionsmentioning
confidence: 99%